Available chemotherapy in Mediterranean fish farming: use and needs - Daniel P. (The use of veterinary drugs and vaccines in Mediterranean aquaculture, 2009)
The availability of aquaculture treatments has changed significantly over the past several years. The European legislation regarding veterinary pharmaceuticals has evolved since 1981 towards important restrictions in the use of medicines to treat food producing animals. The establishment of maximum residue levels (MRLs) for all active substances has raised concerns about the availability of many fish medicines. However, great progress has been made since then and a large number of compounds remain available for the treatment of diseased fish. Currently available and authorised fish medicines are tabulated. Some promising new products have also been developed in recent years.
The Use of Veterinary Drugs and Vaccines in Mediterranean Aquaculture, 2003/05/21-23, Izmir (Turkey)